Improved insect‐proofing: expressing double‐stranded RNA in chloroplasts. Issue 8 (7th March 2018) - Bally, Julia; Fishilevich, Elane; Bowling, Andrew J; Pence, Heather E; Narva, Kenneth E; Waterhouse, Peter M
Abstract: RNA interference (RNAi) was discovered almost 20 years ago and has been exploited worldwide to silence genes in plants and animals. A decade later, it was found that transforming plants with an RNAi construct targeting an insect gene could protect the plant against feeding by that insect. Production of double‐stranded RNA (dsRNA) in a plant to affect the viability of a herbivorous animal is termed trans‐kingdom RNAi (TK‐RNAi). Since this pioneering work, there have been many further examples of successful TK‐RNAi, but also reports of failed attempts and unrepeatable experiments. Recently, three laboratories have shown that producing dsRNA in a plant's chloroplast, rather than in its cellular cytoplasm, is a very effective way of delivering TK‐RNAi. Our review examines this potentially game‐changing approach and compares it with other transgenic insect‐proofing schemes. © 2018 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Producing dsRNA in a plant's chloroplast, rather than in its cellular cytoplasm, appears to be a very effective way of delivering trans‐kingdom (TK) RNAi. We examine this approach.